2012
DOI: 10.1038/ijir.2012.17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vasectomy reversal according to patency for the surgical treatment of postvasectomy pain syndrome

Abstract: This study was conducted to assess outcomes (according to patency) of vasectomy reversal (VR) in qualified patients with postvasectomy pain syndrome (PVPS). A total of 32 patients with PVPS undergoing VR between January 2000 and May 2010 were examined retrospectively. Of these, 68.8% (22/32) completed a study questionnaire, either onsite at the outpatient clinic or via telephone interview. Preoperative clinical findings, preoperative and postoperative visual analogue scale (VAS) pain scores, patency and pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…This study showed a significant difference in improvement of pain scores when comparing the patent and non-patent group. The mean difference in pain scores was 6.00±1.25 (4-8) for the patent group and 4.43±0.98 (3-6) for the non-patent group (20). This may suggest that obstruction and congestion of the epididymis does indeed play a key role in the pathology.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This study showed a significant difference in improvement of pain scores when comparing the patent and non-patent group. The mean difference in pain scores was 6.00±1.25 (4-8) for the patent group and 4.43±0.98 (3-6) for the non-patent group (20). This may suggest that obstruction and congestion of the epididymis does indeed play a key role in the pathology.…”
Section: Discussionmentioning
confidence: 95%
“…While vasectomy reversal may have promising impact on pain control, providers must discuss the possibility of fertility. In fact, 36.4% of men undergoing vasectomy reversal went on to report viable pregnancies (20). With this in mind, Levine suggests epididymectomy for those patients with pain isolated solely to the epididymis or MDSC with diffuse pain.…”
Section: Discussionmentioning
confidence: 99%
“…explored the efficacy of VR according to patency rate in conjunction with pain-free rates in 32 patients and observed a significant difference between the patency and no patency groups in terms of pain reduction and the degree of patient procedural satisfaction. 76 Another retrospective study from the Canadian health system found overall high success rates with lasting resolution of the PVPS during follow-up of 40.5 months. 11/14 patients had improvement in pain after VR (2 out of the 3 patients who did not improve were noted to be azoospermic on semen analysis).…”
Section: Postvasectomy Pain Syndromementioning
confidence: 99%
“…A total of 34% of patients had complete resolution of pain, and 59% of patients reported improvements in pain scores. Lee et al [ 63 ] identified 32 patients who underwent a vasectomy reversal for PVPS and noted that the improvement in the mean preoperative and postoperative VAPS was 6.00±1.25 (range, 4∼8) in the patency group (sperm in the ejaculate) and 4.43±0.98 (range, 3∼6) in the non-patency group (p=0.011). The authors concluded that there was a significant difference in pain reduction in patients who were patent following vasectomy reversal compared to those who remained obstructed.…”
Section: Treatmentmentioning
confidence: 99%